'Born to Run': Remembering C.P. Pow. Issue 1 (5th December 2022) - Neo, Harvey
Abstract : C.P. Pow was my confidant, colleague and (occasional) collaborator for more than 20 years. He had fought a valiant and dignified battle with an aggressive cancer but ultimately succumbed to it in July 2021. I will reminisce a few of the little known traits of Pow which had shaped him to become the conscientious, obliging and humble academic that he was known for.